2020
DOI: 10.3390/coatings10020191
|View full text |Cite
|
Sign up to set email alerts
|

Development of Apatite Nuclei Precipitated Carbon Nanotube-Polyether Ether Ketone Composite with Biological and Electrical Properties

Abstract: We aimed to impart apatite-forming ability to carbon nanotube (CNT)-polyether ether ketone (PEEK) composite (CNT-PEEK). Since CNT possesses electrical conductivity, CNT-PEEK can be expected to useful not only for implant materials but also biosensing devices. First of all, in this study, CNT-PEEK was treated with sulfuric acid to form fine pores on its surface. Then, the hydrophilicity of the substrate was improved by oxygen plasma treatment. After that, the substrate was promptly immersed in simulated body fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
4
1
1
Order By: Relevance
“…In this study, the authors firstly treated the pure PEEK and the 50C-PEEK with H 2 SO 4 . As already reported, pores formation on the surfaces of various types of PEEKs was observed in SEM micrographs [20][21][22]. Moreover, a similar phenomenon was observed even in the case of the 50C-PEEK in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, the authors firstly treated the pure PEEK and the 50C-PEEK with H 2 SO 4 . As already reported, pores formation on the surfaces of various types of PEEKs was observed in SEM micrographs [20][21][22]. Moreover, a similar phenomenon was observed even in the case of the 50C-PEEK in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, the apatite nuclei were precipitated on the surface and in the pores of the PEEKs, and the apatite-forming ability was imparted to the surface of the PEEKs. This method does not require a complicated surface modification process, and it has been confirmed that the apatitic phase was formed within 1 day in the conventional SBF [20][21][22]. In addition, the authors have already reported that the pure PEEK modified with the apatite nuclei showed good bone-bonding ability in rabbit tibia [23].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…る.八尾らは,この微粒子が生理的条件に調整した SBF 中 で早期にアパタイト形成を誘起することを見出し,この微粒 子をアパタイト核(Apatite nuclei)と名付けた (10) .さらに筆 者らはこの現象を応用し,前もって表面に細孔を形成させた 基材の孔内にアパタイト核を析出させることで,金属,セラ ミックスからポリマーにいたる多種多様な材料に高いアパタ イト形成能を付与できることを見出した(図) (11) .筆者ら はこの界面制御技術を用いることで,純チタン (12) ,チタン 合金 (13) (14) 等の,生体活性の発現に長期間を要する硬組織代 替材料のアパタイト形成能が大幅に向上されること,さらに は SUS316L 鋼 (15) ,Co Cr 合金 (16) ,超高分子量ポリエチレ ン (17) ,ポリエーテルエーテルケトン(PEEK) (18)(21) 等の, 骨と結合しない生体不活性な硬組織代替材料へのアパタイト 形成能付与も可能になることを見出した.本稿では,この界 面制御技術の各種生体不活性硬組織代替材料への適用例とし て , ジ ル コ ニ ウ ム 合 金 (22) , イ ッ ト リ ア 安 定 化 ジ ル コ ニ ア (23) ,炭素繊維強化 PEEK (24) へのアパタイト形成能付与に ついて概説するとともに,アパタイト核を用いたアパタイト カプセル (25)(27) の開発についても紹介する.…”
unclassified